Encyclopedia of Maritime and Offshore Engineering 2017
DOI: 10.1002/9781118476406.emoe573
|View full text |Cite
|
Sign up to set email alerts
|

CFDModeling of Diesel Combustion

Abstract: Diesel engines are the most efficient combustion engines today, playing an important role in transport of goods and passengers on land and on sea. The main drivers for the design of future engines is the control of the emissions without sacrificing their advanced fuel economy. These drivers led to important innovations in multiple components of the engine, which, however, complicated the nature of the processes taking place and increased the need for highly accurate simulation frameworks. In the current articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The average sample size needed to meet the error threshold was calculated (Figure 4b) and the process was repeated for thresholds from 1 to 10%. The results of this analysis show that the number of droplets needed to have a reasonably accurate estimate (2 to 4% relative error) of the SMD is between 10 4 and 4x10 4 , while to obtain similar uncertainties on the mean droplet velocity less than a tenth of these amounts are sufficient.…”
Section: Error Evaluation and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The average sample size needed to meet the error threshold was calculated (Figure 4b) and the process was repeated for thresholds from 1 to 10%. The results of this analysis show that the number of droplets needed to have a reasonably accurate estimate (2 to 4% relative error) of the SMD is between 10 4 and 4x10 4 , while to obtain similar uncertainties on the mean droplet velocity less than a tenth of these amounts are sufficient.…”
Section: Error Evaluation and Discussionmentioning
confidence: 90%
“…This analysis showed that the average sample size needed to achieve a certain error is not influenced by the original sample size in the observed range (Figure 7). A more complex behaviour is observed for the SMD, but it is possible to observe that for errors above 2%, the estimate converge for a population around 8x10 4 . This again confirms that the sample used is large enough to draw conclusions above this error threshold.…”
Section: Assumption Check On Sample Size Analysismentioning
confidence: 80%
See 1 more Smart Citation